2011
DOI: 10.1097/fjc.0b013e31821e5649
|View full text |Cite
|
Sign up to set email alerts
|

AKAP Phosphatase Complexes in the Heart

Abstract: Directed protein phosphorylation is indisputably critical for a multitude of cellular processes. A growing body of research demonstrates A Kinase Anchoring Proteins (AKAPs) to mediate a significant number of phosphorylation events in the heart. By acting as molecular tethers for the regulatory subunit of PKA, AKAPs focus the kinase's actions onto specific substrates. In the time since their discovery, the AKAP model has evolved in appreciation of the broader role these scaffolds play in coordinating multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 80 publications
2
27
0
4
Order By: Relevance
“…Sustained TnI and PLB phosphorylation could be due to limited access by protein phosphatases (PP) or continued phosphorylation by PKA. PLB and TnI have been reported to be dephosphorylated by PP1 and PP2A which, like PKA, are tightly regulated and compartmentalized by binding to scaffolding proteins (Redden and Dodge-Kafka 2011). Taken together, our results suggest that the inotropic mechanisms initiated by 5-HT fade quickly with the decline in cAMP, while the lusitropic effects are sustained as also reported in De Maeyer et al (2006), due to maintained phosphorylation of TnI and PLB.…”
Section: Discussionsupporting
confidence: 86%
“…Sustained TnI and PLB phosphorylation could be due to limited access by protein phosphatases (PP) or continued phosphorylation by PKA. PLB and TnI have been reported to be dephosphorylated by PP1 and PP2A which, like PKA, are tightly regulated and compartmentalized by binding to scaffolding proteins (Redden and Dodge-Kafka 2011). Taken together, our results suggest that the inotropic mechanisms initiated by 5-HT fade quickly with the decline in cAMP, while the lusitropic effects are sustained as also reported in De Maeyer et al (2006), due to maintained phosphorylation of TnI and PLB.…”
Section: Discussionsupporting
confidence: 86%
“…It has also been suggested that ISO can induce nuclear HDAC5 export via a PKA-independent but oxidationdependent pathway in adult rat myocytes (42). The discrepancies could be due to the nature of different cell types (they used HEK and cultured neonatal/adult rat ventricular myocytes) and the respective 14-3-3 isoforms present to associate with HDACs (21,43,44) Additionally, substrate specificity of cAMP/PKA signaling is achieved by compartmentalization of localized cAMP gradient via phosphodiesterase isoforms or ␤-arrestins and by association with various AKAP scaffolding subtypes in different cell types (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). Our study provides real-time observation of HDAC5-GFP translocation in adult myocytes to more accurately reflect the fundamentally dominant endogenous signaling pathway in adult ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Calyculin-A is a strong phosphatase inhibitor displaying effect on PP2A (IC 50 approximately 0.5-1 nM) and less effect on PP1 (IC 50 approximately 2 nM), two phosphatases sharing some degree of redundancy. 29,30 To reach a specific Figure 6. Effect of R-roscovitine on protein phosphatase expression and activity in MDCK-hAQP2 cells.…”
Section: Involvement Of Protein Phosphatases In the Regulation Of Aqpmentioning
confidence: 99%